The developing teaching practice model as an effort to improve the quality of mechanical engineering vocational school teachers - Theodorus Wiyanto; Muchlas Samani; Sugiyono Sugiyono (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
This research aims to develop teaching practice program model for mechanical engineering education teacher trainees of State University of Surabaya. This research applied research and development (R & D) design by Borg & Gall in ten steps which are classified into two stages: research and data collection and product development. The research and data collection were conducted by applying qualitative approach through observation, interview, documentation on seven State